2023
DOI: 10.3390/ijms24119478
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diluted Glyphosate Mitigates Its Effects on Artemia salina: Physicochemical Implications

Abstract: Glyphosate is an herbicide widely used in agriculture but can present chronic toxicity in low concentrations. Artemia salina is a common bio-indicator of ecotoxicity; it was used herein as a model to evaluate the effect of highly diluted-succussed glyphosate (potentized glyphosate) in glyphosate-based herbicide (GBH) exposed living systems. Artemia salina cysts were kept in artificial seawater with 0.02% glyphosate (corresponding to 10% lethal concentration or LC10) under constant oxygenation, luminosity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…An essential detail of the method used is how samples are prepared before interacting with the dyes, and this has been described and standardized in previous studies. 18,19,22,26 For all samples, regardless of origin (potentized medicines, water, culture media), a further potency (1cH) of each sample is made in sterile pure water or 30% hydroalcoholic solution (according to the protocol), previously filtered in a 0.22-micrometer mesh filter to avoid eventual contamination. Therefore the sample added to dye solutions corresponds to 1% of the original content.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An essential detail of the method used is how samples are prepared before interacting with the dyes, and this has been described and standardized in previous studies. 18,19,22,26 For all samples, regardless of origin (potentized medicines, water, culture media), a further potency (1cH) of each sample is made in sterile pure water or 30% hydroalcoholic solution (according to the protocol), previously filtered in a 0.22-micrometer mesh filter to avoid eventual contamination. Therefore the sample added to dye solutions corresponds to 1% of the original content.…”
Section: Discussionmentioning
confidence: 99%
“…12 These physico-chemical changes can be monitored through interactions with solvatochromic dyes. [18][19][20][21][22][23][24][25] A recent systematic experimental study has also observed correspondence between biological effects and physico-chemical changes. 26 Solvatochromic dyes have been found to be probes able to track homeopathic potencies both in the laboratory [18][19][20][21][23][24][25][26] and in field studies in the natural environment.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations